On the fundamental unit and class number of certain quadratic function fields, i. (1974)
Let K = ko (x) (√(f(x)) be a function field, where ko  is a finite field of characteristic not equal to 2 and f(x)  is a square free polynomial of even degree and leading  coefficient 1.